Membangun Identitas Diri dalam Terang Iman: Panduan Teologis bagi Generasi Muda - Yakobus Petly Simbong; David Hizkia Tambajong; Petrus Hutabarat (EPIGRAPHE (Jurnal Teologi dan Pelayanan Kristiani), 2023)
Identity crisis represents one of the most significant psychological and spiritual challenges confronting young people in the digital era, where the formation of selfhood is increasingly shaped by social media validation, comparison culture, and conformity pressures. This article aims to theologically examine how Christian faith offers an alternative framework for constructing a robust and psychologically-spiritually healthy self-identity. Employing a qualitative library research method, this article investigates the concept of identity from Reformed and Evangelical theological perspectives, particularly the notion that authentic human identity is rooted in one's status as the image of God (imago Dei) and in relationship with Christ, rather than in achievement, social acceptance, or externally constructed self-image. The study further explores the practical implications of this theology of identity for Christian religious education, pastoral care, and the spiritual formation of young people within both church and educational institutions. Findings indicate that faith-based identity formation can serve as a foundation for psychological resilience, mental health, and character maturity among young people amid the disruptions of digital culture. The article recommends that churches and Christian educational institutions develop formation approaches that intentionally guide young people toward discovering and grounding their identity in the light of God's Word.   Abstrak Krisis identitas merupakan salah satu tantangan psikologis dan spiritual yang paling signifikan dihadapi oleh generasi muda di era digital, di mana pembentukan jati diri semakin dipengaruhi oleh validasi media sosial, budaya perbandingan, dan tekanan konformitas. Artikel ini bertujuan untuk mengkaji secara teologis bagaimana iman Kristen menawarkan kerangka alternatif dalam membangun identitas diri yang kokoh dan sehat secara psikologis-spiritual. Dengan menggunakan metode penelitian kualitatif berbasis studi pustaka (library research), artikel ini menelaah konsep identitas dalam perspektif teologi Reformed dan Injili, khususnya gagasan bahwa identitas sejati manusia berakar pada status sebagai gambar Allah (imago Dei) dan pada relasi dengan Kristus, bukan pada pencapaian, penerimaan sosial, atau citra diri yang dikonstruksi secara eksternal. Kajian ini juga mengeksplorasi implikasi praktis dari teologi identitas ini bagi pendidikan agama Kristen, pendampingan pastoral, dan pembinaan rohani generasi muda di gereja maupun lembaga pendidikan. Hasil kajian menunjukkan bahwa penguatan identitas berbasis iman dapat menjadi fondasi bagi ketahanan psikologis, kesehatan mental, dan kedewasaan karakter generasi muda di tengah disrupsi budaya digital. Artikel ini merekomendasikan agar gereja dan lembaga pendidikan Kristen mengembangkan pendekatan pembinaan yang secara intensional mengarahkan generasi muda untuk menemukan dan mengokohkan identitas mereka dalam terang firman Tuhan.